Effect of hydrogen peroxide and universal adhesive application on the bond strength of glass fiber posts - Fernando Dalitz; Orides Ferrari de Oliveira Junior; Raisa Carolina Hintz; Gisele Maria Correr; Leonardo Fernandes da Cunha; Carla Castiglia Gonzaga (Universidade Estadual de Campinas, 2017)
Aim: This study aims to evaluate the effect of different surface treatments on the bond strength of glass fiber posts. Methods: Ninety unirradicular premolars had their crowns removed and were endodontically treated. After 24h, post spaces were prepared and the roots (n=15) were divided into six groups according to the post surface treatment: NT - no treatment, UA - universal adhesive (Single Bond Universal), SUA - silane (Prosil), followed by universal adhesive, H - H2O2 (Whitness HP Maxx, 35%, gel, 1 min), HUA - H2O2, followed by universal adhesive, and HSUA - H2O2, followed by silane and universal adhesive. The posts were cemented with dual-cured resin cement (RelyX Ultimate). Bond strength was evaluated with pull-out test (0.5 mm/mim) after 24h-storage in distilled water at 37oC. Data were submitted to ANOVA and Tukey's test (α=5%). Results: HSUA group showed the highest bond strength value (236.5 N) followed by HUA (206.5 N), NT (194 N) and SUA (184 N) groups. UA group showed the lowest bond strength value (60 N). Conclusion: The use of H2O2, the silane application or the combination of these two treatments significantly increased bond strength values in groups in which the universal adhesive was used. A simplified procedure, such as cleaning with alcohol, can be recommended as surface treatment for the cementation of glass fiber posts.